Технологии межсервисной связи в микросервисной архитектуре программных систем - Синкевич, М. Э. (ХНУРЕ, 2019)
The given work considers the interservice communication methods used in the microservice architecture of software systems. Since the connection between microservices should be efficient and reliable, with a large number of small services interacting to perform a single transaction, this can be a challenge, therefore, it is necessary to identify ways to achieve better efficiency. Consider the main approaches to the process organizing of interaction and identify a compromise between asynchronous and ynchronous messaging which significantly affect the work of the software.